Application of Actuarial Method in Criminal Law of the Kingdom of Sweden - Petrović, Ivana D. (Zbornik Instituta za kriminološka i sociološka istraživanja, 2015)
The Nordic model of criminal policy attracts the attention of experts and theoreticians, given to the fact that it is effective in reducing criminal recidivism in the long-term historical perspective, on the one hand, while on the other hand, it pays considerable attention to the structural respect for fundamental human rights and freedoms. As a typical representative of the Nordic model of criminal law policy, the Kingdom of Sweden arouses scientific interest, particularly in relation to the fact of the forensic assessment of suspects and defendants in the era of the rule of actuarial justice. In accordance with the previous, the goal of this paper is to impose orientation towards reviewing the most important provisions of national criminal legislation by content analysis, and in conjunction with the application of actuarial risk assessment methods, which will enable the offender to manifest threatening behaviour within a certain period. The significance of applied content analysis of criminal law regulations of the jurisdiction of the Kingdom of Sweden can be found in practical solutions of the national normative legal sources concerning the use of idiographic-structured probabilistic assessment of suspects and defendants in determining criminal sanctions, external classification of offenders and determination of corrective programs.